Insight into the adsorption mechanism of cationic dye onto biosorbents derived from agricultural wastes. Issue 9 (2nd September 2017) - Tran, Hai Nguyen; You, Sheng-Jie; Nguyen, Tien Vinh; Chao, Huan-Ping
ABSTRACT: This study investigated the phenomenon and mechanism of adsorption of methylene green 5 (MG5) on three pristine biosorbents: golden shower pod (GS), coconut shell (CC), and orange peel (OP). The results showed that the biosorbents possessed low specific surface areas, but abundant functional groups. Adsorption was strongly affected by the solution's pH and ionic strength. As revealed in the kinetic study, equilibrium was rapidly established, requiring low activation energies; a removal rate of 30%–87% was achieved within 1 min. The maximum Langmuir adsorption capacities at 30°C exhibited the following order: GS (106 mg/g) > OP (92 mg/g) > CC (59 mg/g). Thermodynamic experiments suggested that the adsorption occurred spontaneously (−ΔG°) and exothermically (−ΔH°). The primary adsorption mechanisms involved electrostatic attraction, hydrogen bonding formations, and n-π interaction. Thermogravimetric analysis (TGA) revealed that three biopolymer components (i.e., hemicellulose, cellulose, and lignin) played controlling roles in the adsorption process. Thus, these three agricultural residues can be considered potential low-cost adsorbents for efficient dye adsorption applications.